Four new species of Adenocalymma (Bignoniaceae) and a key to the species from southeastern Brazil - Udulutsch, Renata Giassi [UNESP]; Assis, Marco Antonio de [UNESP]; Dias, Pedro (Wiley, 2013)
Four new species of Adenocalymma (Bignoniaceae, Bignonieae) from southeastern Brazil are described and illustrated: A. aurantiacum, characterized by dark orange and infundibuliform corolla; A. cinereum, characterized by shrubby habit, greyish inflorescence, infundibuliform corolla, and exserted stamens; A. gibbosum, characterized by gibbous and orange corolla and an inflorescence with dendritic trichomes; and A. sessile, characterized by sessile leaves and gibbous corolla. A discussion on the relationships of the new taxa and a key to all 29 species of Adenocalymma reported from southeastern Brazil are provided. © 2013 The Authors. Nordic Journal of Botany © 2013 Nordic Society Oikos.
Keywords: dicotyledon; habitat type; identification key; new species; species diversity; taxonomy; Brazil; Adenocalymma; Bignoniaceae